Green Tea Product Development: Integrating QFD with PLS-SEM, BMC, and AHP for Optimal Business Growth - Azrifirwan, Azrifirwan; Husna, Irma Ayu Sahanatul; Ismanto, Sahadi Didi (Green Engineering Society, 2025)
Green tea offers numerous health benefits; however, its market sales remain relatively low. PT Mitra Kerinci, the producer of the Likicha brand green tea, reported that only 38% of its annual production was absorbed by the market. This situation underscores the need for a strategic development plan to enhance sales performance. Therefore, an integrated approach combining PLS-SEM, BMC, QFD, and AHP methods was employed to formulate a strategy to increase the sales volume of Likicha green tea. This study aimed to identify consumer preferences for green tea products to develop a product strategy that enhances market absorption. The findings of this study indicate that consumer purchase intentions for green tea are influenced by health benefits, product packaging attributes, and price. A business mapping of the green tea industry was conducted to obtain a comprehensive internal and external analysis. The QFD data analysis identified technical requirements and prioritized component needs for improving green tea production. These results were then used to formulate criteria and strategic alternatives aimed at increasing green tea sales volume. The results indicate that product quality holds the highest priority among the criteria, with a weight of 64.3%. Among the strategic alternatives, sourcing high-quality tea leaves and optimizing processing methods emerged as the top priority, with a weight of 26.2%.